2022
DOI: 10.1109/access.2022.3186325
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Public Service Delivery Smartness and Impact on Citizens’ Well-Being

Abstract: Public sectors are increasingly adopting emerging technologies to innovate and deliver smart services to enhance citizens' overall well-being. Although the idea of smartness in public sector service innovations has been explored from the perspective of service providers, limited study has been done from the perspective of end users. Furthermore, the impact of smart service delivery on citizens' quality of life has been widely studied quantitatively, but qualitative evidence has been sparse. This paper aims to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
(173 reference statements)
0
2
0
Order By: Relevance
“…The findings provide valuable insights for enhancing the accessibility, empathy, and responsiveness of financial aid services at a university, ultimately contributing to a more inclusive and supportive environment for all students. The study's recommendations offer a pathway for addressing the identified challenges and improving the overall quality of service delivery within the Department, aligning with the broader literature on service quality and delivery in various contexts (Entwistle et al, 2012;Hartanti et al, 2022;Restall et al, 2017).…”
Section: Discussionmentioning
confidence: 93%
“…The findings provide valuable insights for enhancing the accessibility, empathy, and responsiveness of financial aid services at a university, ultimately contributing to a more inclusive and supportive environment for all students. The study's recommendations offer a pathway for addressing the identified challenges and improving the overall quality of service delivery within the Department, aligning with the broader literature on service quality and delivery in various contexts (Entwistle et al, 2012;Hartanti et al, 2022;Restall et al, 2017).…”
Section: Discussionmentioning
confidence: 93%
“…Effective leadership is meant by the results of previous research, namely when a leader has a reliable leadership style [16] and continues to make changes consistently and has the initiative to make breakthroughs [15]. When public service innovation can be implemented properly, it can increase the efficiency, effectiveness, transparency and accountability of public services [17]- [19] community satisfaction, and welfare [20], [21]. The second analysis, namely the implementation of public service innovation cannot be separated from collaboration.…”
Section: Resultsmentioning
confidence: 99%